A Flail Anterior Tricuspid Leaflet Secondary to Anteroposterior Papillary Muscle Rupture in a Neonate. Issue 5 (4th February 2014) - Yemul, Madhusudan Ambadas
Mini‐Abstract This article is a summary of a case of a neonate who presented with tricuspid valve insufficiency associated with papillary muscle rupture but, however, showed no signs of cardiac failure. The transthoracic three‐dimensional echocardiographic findings in this case are described in detail herein.